Business Plan : Yummy Milk Sdn Bhd / Zurina Mohd Arshad ... [et al.] - Mohd Arshad, Zurina; Mohd Nawi, Ummi Khairunnisa ‘; Boinan, Nur Syafiqah; Abdullah, Nadia; Azmi, Nur Nadhirah (2008)
Name of our business is Syarikat Yummy Milk Sdn. Bhd, Our form of business is private limited company. The nature of business is fresh milk production. We choose this type of business because we can share the profit equally among ourselves. Our objective is to run this business because we want to provide healthy milk to the society especially student. We decide to choose this business because milk as one type of supplement food that have a lot of benefit to the people. Furthermore, this kind of business has potential to grow in long term period. In addition, from our research from industry overview we found that this business has wide scope of production and market. Since 1998, milch stock is not in consistency condition but milk uses is increase. In 2001, only 26184 milch cows was livestock in Malaysia, meanwhile milk use achieve 1097.96 billion liter. Dasar pertanian Negara Ke-3 (DPN 3) encourage the milch production by private sector through modern and great alternatives. This industry can be a suitable investment and also can be achieving by having variety of cow’s heredity that provide by Jabatan Perkhidmatan Haiwan. This new heredity was produce by emphasizing local environment factor to produce an optimum milk production. Import milk cow for Peninsular of Malaysia on 2001 increase about 21% from 2000 to 2001 at price RM1.4 billion.Price of cow milk different with other manufacturer and the price around RM 1.50 to RM 4.00 for a liter.